The Evolution of Public Sector Leadership in the Era of Digital Transformation - Sugiyanto, Heri (Universitas Indonesia Mandiri, 2025)
Digital transformation has brought significant changes to the public sector, demanding adaptive, data-driven, and collaborative leadership to enhance efficiency and service quality. This research aims to identify the role of transformational, data-driven, and cross-sectoral leadership in managing digital transformation in the public sector, with a focus on the challenges and opportunities involved. A qualitative approach through a literature review is employed to analyse various relevant academic sources, including journals, books, and reports from 2015 to 2024. Data collection techniques involve searching academic databases such as Scopus, Web of Science, and Google Scholar. The findings reveal that transformational leadership significantly contributes to the success of digital transformation by fostering innovation and driving organisational cultural change. Data-driven leadership enhances accountability and efficiency, while cross-sectoral collaboration strengthens the digital ecosystem through multi-stakeholder participation. These findings also highlight key challenges, including organisational cultural resistance, technological infrastructure limitations, and data security issues. The study concludes by emphasising the importance of public sector leaders integrating technology-driven, data-informed, and participatory strategies to design sustainable digital transformations. The practical implications of this research include strategic guidance for the public sector to navigate dynamic digital changes.